2007
DOI: 10.1186/1471-2318-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of information and support interventions for caregivers of people with dementia

Abstract: BackgroundDementia is an important health and social care problem and is one of the main causes of disability in later life. The number of families affected by dementia will dramatically increase over the next five decades. Despite the implications for health and social care services in the future, the overwhelming majority of care for people with dementia takes place away from health care settings. Providing informal care for someone with dementia can be psychologically, physically and financially expensive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
273
0
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(289 citation statements)
references
References 19 publications
5
273
0
11
Order By: Relevance
“…It included only randomized clinical trials and concluded that, at that time, there was no evidence on the uniform effectiveness of interventions, which were based on information and caregiver support (25) .…”
Section: * Ig -Intervention Group and Cg -Control Groupmentioning
confidence: 99%
“…It included only randomized clinical trials and concluded that, at that time, there was no evidence on the uniform effectiveness of interventions, which were based on information and caregiver support (25) .…”
Section: * Ig -Intervention Group and Cg -Control Groupmentioning
confidence: 99%
“…The time period over which many health outcomes are measured in most studies, 6 months to one year, do not capture the full effects because caregivers often have many more years of caregiving in front of them (Thompson et al 2007). In addition, once a caregiver ceases being a caregiver, we know little about whether he or she will regain the health status lost due to caregiving, or whether the health effects will persist.…”
mentioning
confidence: 99%
“…Second: How can support for the family caregivers be optimized? Which factors influence the decision whether support offers (Gallagher- Thompson and Coon 2007;Pinquart and Sörensen 2006;Thompson et al 2007)-assuming areawide availability-are actually utilized or not? This study deals with the second question particularly regarding caregiver counselling.…”
Section: Introductionmentioning
confidence: 99%